A trajetória de Anísio Teixeira : princípios e experiências para a formação de professores em Mato Grosso - Silva Junior, Rosan Chaves (2023)
In this dissertation, we aim to investigate the theme "Teacher Education" through accounts and research concerning the spheres of Anísio Teixeira's activities, as well as the perspectives of researchers and colleagues who followed and analyzed his legacy. The research is directed towards comprehending teacher education in Anísio Teixeira's conception and the significance of "science, labor, and democracy" as guiding principles in the establishment of mechanisms for teacher training. The methodology is constructed upon a bibliographical survey, seeking to understand the processes of Teacher Education by juxtaposing the experiences of the philosopher and education administrator, Anísio Teixeira. This spans from his involvement with the Manifesto dos Pioneiros da Educação Básica (Manifesto of the Pioneers of Basic Education), the creation of CBPE (Brazilian Center for Educational Research), and the conceptualization and realization of Escola Parque, alongside the opportunities and potentials that emerged in the field of teacher education in Mato Grosso with the establishment of the Centro de Formação e Atualização de Profissionais da Educação Básica de Mato Grosso (Center for Training and Updating of Basic Education Professionals of Mato Grosso - CEFAPRO). The configuration of the research will be carried out through a triad of Qualitative Epistemology, Bibliographical Research, and the Constructive-Interpretative Methodology by González Rey. We aim to establish connections with contemporary authors such as Morin, Prigogine, Brandão, José Pacheco, Darcy Ribeiro, Bernardete Gatti, and Streck, within a humanistic, scientific, and labor-related perspective. This involves relating the possibilities of understanding current challenges and thoughts in Teacher Education. In conclusion, it is expected that this research can contribute to the essential revival of Anísio Teixeira in discussions about the construction of a unified education system, as well as stimulate reflection on the necessity of CEFAPRO's role as an autonomous center for the organization, reflection and planning of educational actions and teacher training.